The Influence of Tensile Strength Test Values on the Elongation of Eco-Friendly Paper - Ety Jumiati; Miftahul Husnah (Journal of Technomaterial Physics, 2025)
Paper is a thin material in the form of sheets. Environmentally friendly paper is obtained from natural materials derived from discarded waste. This study aims to investigate the characteristics and the effect of elongation values on the tensile strength of the produced paper. The composition variations between taro peel and oil palm frond fibers in paper production were 30%:70% (sample A); 40%:60% (sample B); 50%:50% (sample C); 60%:40% (sample D); and 70%:30% (sample E). The pulp preparation process was carried out using the soda method, while the drying process was conducted naturally at room temperature for 12 hours. The results of the paper characterization for samples A, B, C, D, and E showed tensile strength values of 5.2570 kN/m, 6.2875 kN/m, 7.1985 kN/m, 8.8975 kN/m, and 9.5060 kN/m, respectively, while the elongation test values were 1.09%, 1.12%, 1.15%, 1.24%, and 1.52%. These values have met the requirements for printing paper grade A according to SNI 7274:2008. The results indicate that the higher the composition of oil palm frond fibers used, the greater the tensile strength and elongation values of the paper.